The Fundamental and Rigidity Theorems for Pseudohermitian Submanifolds in the Heisenberg Groups (Journal of Mathematical Study, 2021)
In this paper, we study some basic geometric properties of pseudohermitiansubmanifolds of the Heisenberg groups. In particular, we obtain the uniqueness andexistence theorems, and some rigidity theorems.